Applications of image-guided locoregional transarterial chemotherapy in patients with inoperable colorectal cancer: a review - Meng, Wenjun; Pan, Lu; Huang, Li (Frontiers in Oncology, 2024)
With the development of comprehensive treatment, locoregional transarterial chemotherapy has become an alternative conversion therapy, palliative therapy, and neoadjuvant therapy for many solid malignant tumors. Locoregional transarterial chemotherapy, which is most frequently used for treating liver cancer, has the characteristics of high regional efficacy and few systemic adverse reactions. In recent years, the number of relevant reports of locoregional chemotherapy for treating initially inoperable colorectal cancer (CRC), including non-metastatic and metastatic CRC, has gradually increased. However, the specific treatment options for such locoregional therapy are not the same, and its indications, medication regimens and combined treatments have not reached any consensus. In this review, the application status of locoregional transarterial chemotherapy in primary and metastatic CRC patients has been reviewed and summarized to provide a reference for future clinical work and scientific research.